Oral coinfection can stress peripheral lymphocyte to inflammatory activity in leprosy - Motta,Ana Carolina Fragoso (2013)
INTRODUCTION: This study evaluated the intracellular profile of interleukin-2 (IL-2), interleukin-4 (IL-4), interleukin-10 (IL-10) and interferon-γ (IFN-γ) in peripheral blood mononuclear cells (PBMCs) from leprosy patients based on oral infections presence to determine whether these coinfections could be associated with pro-inflammatory activity in leprosy. METHODS: Leprosy patients regardless of clinical form and specific leprosy treatment (n=38) were divided into two groups: Group I - leprosy patients with oral infections (n=19), and Group II - leprosy patients without oral infections (n=19). Non-leprosy patients presenting oral infections were assigned to the control Group (n=10). Intracellular IL-2, IL-4, IL-10 and IFN-γ production was evaluated by flow cytometry (FACS) before and 7 days after controlling the oral infection in the Group I, before and 7 days after dental prophylaxis in the Group II, and during oral infection process in control Group. RESULTS: Low percentages of CD3+ lymphocytes bearing IL-2, IL-10 and IFN-γ were observed in the Group I and Group II at baseline and 7 days after therapy or prophylaxis compared to controls. Group I showed reduced percentages of IL-4 at baseline and 7 days after therapy compared to controls, or at baseline of Group II, and the Group II showed reduced percentages of CD3+ cells bearing IL-4 compared to control. An increase of the percentages of CD3+cells bearing IL-4 was observed in the Group I after the oral infections treatment. CONCLUSIONS: The occurrence of oral infections favors the intracellular cytokines expression and, probably, the inflammatory reaction operating as a stimulatory signal triggering the leprosy reactions.